Sleep dependent consolidation of gross motor sequence learning with motor imagery. (July 2022) - Debarnot, Ursula; Metais, Angèle; Digonet, Guillaume; Freitas, Emilie; Blache, Yoann; Saimpont, Arnaud
Abstract: Acquisition of gross motor sequence learning with physical and mental training elicits gains in performance. However, the effects of sleep or daytime consolidation after both types of practice remain unclear, especially the effects upon the goal- and movement-based components of a gross motor sequential task. The main purpose of this study was to test the effect of physical practice (PP) and motor imagery practice (MIP) on the acquisition and consolidation processes of gross motor sequence learning. Seventy-six participants were tested before and after PP or MIP on a whole-body sequential paradigm, following either a night of sleep (PPsleep and MIPsleep groups) or an equivalent daytime period (PPday and MIPday groups). Control groups without training were tested following similar timespans (CTRLsleep and CTRLday groups). The number of sequential movements and the centre of mass displacement – corresponding to goal and movement-based components, respectively – were assessed. Results showed that relative to the CTRL groups, the PP and MIP groups improved performance during acquisition. Importantly, only the MIPsleep group further improved performance after a night of sleep; participants of other groups stabilised their performance after consolidation. Additionally, the number of sequential movements and the centre of mass displacement evolved conjointly without being influenced by the type of training or the nature of the consolidation. To conclude, these results confirm that sleep contributes to the consolidation of gross motor sequence learning acquired with MIP but not PP. The relationship between the goal- and movement-based components of a gross motor sequential task is discussed. Highlights: Gross motor learning with both physical and motor imagery practice improve performance during acquisition. Sleep-dependent gains in performance are observed only after motor imagery practice. Physical practice performance is stabilised following both sleep and daytime consolidation. Goal- and movement-based contents of gross motor learning evolve conjointly regardless of the nature of consolidation.